2016
DOI: 10.1007/s00204-016-1720-0
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8 Tetrachlorodibenzo-p-dioxin-induced RNA abundance changes identify Ackr3, Col18a1, Cyb5a and Glud1 as candidate mediators of toxicity

Abstract: 2,3,7,8 Tetrachlorodibenzo-p-dioxin (TCDD) is an aromatic, long-lived environmental contaminant. While the pathogenesis of TCDD-induced toxicity is poorly understood, it has been shown that the aryl hydrocarbon receptor (AHR) is required. However, the specific transcriptomic changes that lead to toxic outcomes have not yet been identified. We previously identified a panel of 33 genes that respond to TCDD treatment in two TCDD-sensitive rodent species. To identify genes involved in the onset of hepatic toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…As the study of TCDD effects was performed using a different setting, and a considerable number of genes were not available on both platforms (only a 9534 gene overlap), a less stringent significance threshold of FDR < 0.05 was used to consider overlap across studies. Shortly after a single exposure to either C2 or TCDD, 11 genes demonstrated changes to RNA abundance in the same direction with similar magnitudes (Figure 4a); these include a number of ‘AHR-core’ genes ( Cyp1a1 , Cyp1a2 , Nqo1 , and Cyb5a [60]), as well as Glrx and RGD1310209 (a gene similar to EIG121 that is involved in regulation of autophagy). Similarly, 10 days after initial exposure to either C2 or TCDD, 12 genes showed changes to RNA abundance of similar size and direction, again including Cyp1a1 , Cyp1a2 , Nqo1 , Glrx , and RGD1310209 (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…As the study of TCDD effects was performed using a different setting, and a considerable number of genes were not available on both platforms (only a 9534 gene overlap), a less stringent significance threshold of FDR < 0.05 was used to consider overlap across studies. Shortly after a single exposure to either C2 or TCDD, 11 genes demonstrated changes to RNA abundance in the same direction with similar magnitudes (Figure 4a); these include a number of ‘AHR-core’ genes ( Cyp1a1 , Cyp1a2 , Nqo1 , and Cyb5a [60]), as well as Glrx and RGD1310209 (a gene similar to EIG121 that is involved in regulation of autophagy). Similarly, 10 days after initial exposure to either C2 or TCDD, 12 genes showed changes to RNA abundance of similar size and direction, again including Cyp1a1 , Cyp1a2 , Nqo1 , Glrx , and RGD1310209 (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…The protein Glud1b plays a key role in nitrogen and glutamate metabolism, and also in the energy homeostasis (https://zfin.org/ZDB-GENE -030828-1). The human ortholog GLUD1 is a serum marker for hepatotoxicity along with ALT and AST (Hu et al, 2014), and Glud1 was identified as a marker in TCDD-induced hepatotoxicity in rats (Watson et al, 2017). The Eno1a protein is involved in glycolysis and was previously reported to be differentially expressed in zebrafish embryo after exposure to CsA (Ponnudurai et al, 2012), supporting a role in hepatotoxicity.…”
Section: Discussionmentioning
confidence: 98%